Dampak Kenaikan Ongkos Kirim terhadap Elastisitas Permintaan Produk di Market Place Studi Kasus: Shopee - Etty Zuliawati Zed; Dea Aprilia; Dhea Aulia Trifadilah; Amelia Yunika Putri (Asosiasi Riset Ekonomi dan Akuntansi Indonesia, 2025)
This research aims to analyze the impact of increased shipping costs on the price elasticity of demand for products on the Shopee marketplace platform. The method used in this study is qualitative, focusing on secondary data sourced from various literatures, research findings, scientific publications, and relevant public data. Through a comparative analysis approach and interpretation of the available data, this study intends to identify patterns, trends, and inconsistencies related to the impact of increased shipping costs on the price elasticity of demand for products on marketplace platforms like Shopee. The results of this study are expected to help sellers and Shopee address the impact of increased shipping costs on market demand. Additionally, academically, this research expands the understanding of product demand reactions to changes in shipping costs on marketplace platforms.